Peculiarities of building a program of physical therapy for people of the second mature age with diabetes of the 2nd type of moderate severity - Sorvenkova , Olena; Sychov , Sergiy; Naumenko , Natalia (The Ukrainian Scientific Medical Youth Journal, 2024)
аccording to the WHO, almost 422 million people worldwide have diabetes, and 1.5 million deaths are directly related to this disease every year. Men are more prone to developing type 2 diabetes than women. According to scientists from the University of Eastern Finland, this may be due to the fact that the male body accumulates more iron than the female body. Excessive iron accumulation is a known risk factor for the development of type 2 diabetes in hereditary hemochromatosis, a disorder that causes the body to absorb too much iron from foods (BBC NEWS, 2023). In Ukraine, more than 1 million patients with diabetes mellitus were identified, and their number exceeded 140 million people on the globe, and most of them (85-90%) suffer from diabetes type 2 (in Ukraine, there are 793,413 people - 86.7%). The authors developed an author's program of physical therapy for 2 adults with diabetes type 2 of moderate severity, which included the use of kinesiotherapy, massage, physiotherapy, mechanotherapy and diet therapy. After carrying out this program, the patients observed a significant improvement in the functional and physiological state of the body, as well as the quality of life. Physiotherapeutic agents were used to reduce blood sugar and prevent complications in type 2 diabetes of moderate severity. The results of the conducted research indicate that the developed comprehensive program of physical therapy measures for 2 mature age patients with type 2 diabetes mellitus of medium severity has a more effective effect on the restoration of the functional state of patients with diabetes mellitus type 2 of medium severity than generally accepted program of the Spina + kinesiotherapy center. This conclusion was made on the basis of the assessment of indicators of blood sugar reduction, body weight and assessment of quality of life according to the SF-12 questionnaire.